Clinical and Functional Characterization of Novel INSR Variants in Two Families With Severe Insulin Resistance Syndrome - Zhou, Qiaoli; Yu, Jing; Yuan, Xuewen; Wang, Chunli; Zhu, Ziyang; Zhang, Aihua; Gu, Wei (Frontiers in Endocrinology, 2021)
Objective: Defects in the insulin receptor (INSR) gene cause various severe insulin resistance conditions, including Donohue syndrome (DS), Rabson-Mendenhall syndrome (RMS) and type A insulin resistance (type A-IR). This study aimed to investigate the clinical characterization and molecular defects in three Chinese children with INSR-related insulin resistance syndrome. Methods: We reviewed the clinical data of three Chinese children with INSR-related insulin resistance syndromes from two unrelated families. Genetic analysis was performed using whole-exome sequencing and the effects of the novel variants were further assessed by in vitro functional assays. Results: The proband with type A-IR presented with acanthosis nigricans, hypertrichosis, and euglycemia with mild insulin resistance in early childhood. His sister presented with features typical of type A-IR and was diagnosed with diabetes mellitus with severe insulin resistance at the age of 9.8 years. The proband with DS showed typical dysmorphic characteristics, severe intrauterine growth retardation, extreme insulin resistance, fasting hypoglycemia and postprandial hyperglycemia from birth. The heterozygote variants c.[3670G>A]; c.[3614C>T] were identified in both siblings with type A-IR; and c.[749_751del]; c.[3355C>T] in the patient with DS. In vitro studies showed that the novel variant c.749_751del [p.(Thr250del)] in the α-subunit, reduced expression of the mature INSR protein and severely impaired INSR function. In contrast, the novel variant c.3670G>A [p.(Val1224Met)] in the β-subunit had no effect on receptor processing and autophosphorylation. Conclusion: Our study details the clinical features of three patients with type A-IR and DS, and identified two novel variants in the INSR gene. Biochemical analysis of the mutant insulin receptor suggested that severity of the phenotype may be predicted on the basis of genotype.